Sunitinib for adenocarcinoma of the rete testis: a case report - Li, Kezhen; Chen, Di; He, Mingdong; Yu, Jun; Mi, Hua (Frontiers in Oncology, 2024)
Background: Adenocarcinoma of the rete testis (AORT) is an extremely rare and aggressive tumor with a poor prognosis. Its etiology and pathological characteristics have not been extensively studied, making accurate diagnosis and appropriate management challenging. AORT, an invasive testicular tumor with a mortality rate of 46%, treatment typically involves radical orchiectomy, retroperitoneal pelvic lymph node dissection (RPLND), adjuvant chemotherapy, and/or ongoing monitoring, but the response to conventional radiation and chemotherapy is limited. At present, no effective targeted therapy for AORT has been found.